Still honking more scenes from Malaysian life - Teh, Lydia (MPH Group Publishing Sdn Bhd, 2014)
Though it has been over seven years since Lydia Teh "honked" her way into the hearts of readers through her best-selling Honk! If You're Malaysian, it appears things haven't changed much since it was published. Yes, she is still honking. She is, after all, the typical Malaysian next door. In Still Honking: More Scenes from Malaysian Life, Teh continues to hold up a mirror to the Malaysian psyche and way of life. Her light-hearted anecdotes capture the essence of being Malaysian. True-blue Malaysians and foreigners alike will still recognise the characters and situations in these snippets of what happens in the average (and not-so-average) Malaysian backyard and laugh (or maybe cry) at memories of something similar. Some might be sad at the realisation that little has changed in this multicultural melting pot of a nation, but many others, perhaps, wouldn't want it any other way.